Outperforming IMF Forecasts by the Use of Leading Indicators - Katja Drechsel; Sebastian Giesen; Axel Lindner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This study analyzes the performance of the IMF World Economic Outlook forecasts for world output and the aggregates of both the advanced economies and the emerging and developing economies. With a focus on the forecast for the current and the next year, we examine whether IMF forecasts can be improved by using leading indicators with monthly updates. Using a real-time dataset for GDP and for the indicators we nd that some simple single-indicator forecasts on the basis of data that are available at higher frequency can signi cantly outperform the IMF forecasts if the publication of the Outlook is only a few months old.
Keywords: C52; C53; E37; 330